Arbuscular mycorrhizal root colonisation and the subsequent host plant response in young grapevines in a South African commercial vineyard - Meyer, Andre Harold (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2003.